Determination Of The Nucleotide Sequence Of Recombinant Plasmid Pbx6 Containing A Xylanase Gene From Fibrobacter Succinogenes S 85 - Suryadi, Yadi (2001)
pBX6 is a recombinant plasmid containing a 3 kb fragment of insert D NA from Fibrobacter succinogenes S 85 genomic DNA which encodes xylanase activity. The recombinant plasmid pBX6 has shown xylanase activity when grown on RBB-xylan plates supplemented with ampicillin. Restriction mapping of the plasmid established the presence of single sites for EcoRI, Kpnl, Apal, Saci, EcoRV and Pstf. This work was focussed on nucleotide sequence determination of recombinant plasmid pBX6 containing a xyJanase gene from F. succinogenes S 85. The primer walking strategy was performed to complete manual sequencing, following the protocol cycle sequencing of Sanger dideoxy chain termination. Custom synthesis primer was designed and constructed from 3' end of the preceding sequence on both strands.